Prevalence and haemato-biochemical changes of tick-borne haemoparasitic diseases in crossbred cattle of Haryana, India - GANGULY, ANITA; BISLA, R S; SINGH, HARPREET; BHANOT, VANDNA; KUMAR, ANKIT; KUMARI, SONU; MAHARANA, BISWA RANJAN; GANGULY, INDRAJIT (The Indian Journal of Animal Sciences, 2017)
Theileriosis, babesiosis and anaplasmosis are the important tick-borne haemoparasitic diseases (TBHDs) of ruminants, mostly prevalent in the tropics and subtropics, pose a substantial economic losses to dairy industry particularly in developing countries. Here we have discussed the prevalence and haemato-biochemical changes of these TBHDs in eastern Haryana, India. The prevalence of TBHDs in crossbred cattle was studied by screening 10,776 clinically suspected blood samples during the period of July 2010 to June 2015. Among the screened samples, 4,454 animals (41.33%) were found to be TBHDs-positive. Out of 4,454 positive cases, Theileria annulata, Babesia bigemina, Anaplasma marginale and mixed infections were reported to be 80.62% (n=3591), 11.52% (n=513), 4.06% (n=180), and 3.82% (n=170), respectively. T. annulata was more prevalent during rainy season (37.26%) followed by summer (32.49%) and winter (26.37%); whereas B. bigemina and A. marginale were more prevalent in summer (6.26% and 1.94%, respectively) followed by winter (4.79% and 1.86%, respectively) and rainy season (3.14% and 1.28%, respectively). Significant decrease of values like Hb, TEC, PCV in TBHDs observed in infected animals compared to healthy control groups, indicated haemolytic anaemia. Hypoglycemia was also observed in the infected group. High activity of ALT and AST was noted among the animals of infected group and may be associated with hepatic injury or due to muscle trauma caused by prolong clinical recumbency. Year-wise an increasing trend of prevalence of tick-borne haemoparasitic diseases and the presence of seasonal variation in occurrence of T. annulata and B. bigemina infection was observed in the present study. T. annulata was found to be the most prevalent and endemic haemoparasites in this region. Findings of the present study have profound clinical significance towards controlling tick-borne diseases as well as improving animal health and productivity.